The effect of scenario-based training on the Core competencies of nursing students: a semi-experimental study - Mohammad Sadeghi; Monirsadat Nematollahi; Jamileh Farokhzadian; Zohreh Khoshnood; Mostafa Eghbalian (BMC, 2023)
Abstract Introduction Competency is defined as the variety of skills and knowledge required to perform a specific task. Due to the specificity of pediatric nursing, students face some challenges in acquiring core competencies. Therefore, the use of new training methods in pediatric nursing is necessary. One of the modern learning methods is learning based on clinical scenarios. Thus, this study aimed to investigate the effect of scenario-based education on the core competencies of nursing students. Method This quasi-experimental study employed a pre-test and post-test design. All participants (n = 72) were selected via the census method and randomly divided into intervention (N = 33) and control groups (N = 40). The data were collected using a demographic information questionnaire and the Nursing Students' Clinical Competencies Questionnaire. Before the intervention, both groups completed the pre-tests. After one month, the students in both groups completed post-tests. Results The average score of core competencies for the students in the intervention group after the training (247.05, SD = 36.48) increased compared to before the intervention (229.05, SD = 36.58) (P > 0.05). The average score of the core competencies for the students in the control group after the training was 240.76 (SD = 35.36) compared to 235.56 (SD = 27.94) before the intervention, with no significant difference (P < 0.05). The independent t-test did not show a significant difference between the control and intervention groups before and after the intervention (P > 0.05). Conclusion The results indicated the effectiveness of scenario-based training on the core competencies of students in the intervention group. Accordingly, nursing administrators and professors are recommended to incorporate new scenario-based teaching and learning methods in educational programs of universities. It is also necessary to conduct more research into the effectiveness of this method in combination with other training methods like team-based and problem-based training.